Effects of combined measures to minimize white efflorescence formation on dry fermented sausages co‐extruded with alginate casings. Issue 8 (15th July 2020) - Hilbig, Jonas; Wenzel, Hannes; Herrmann, Kurt; Weiss, Jochen; Gibis, Monika
Abstract : Abstract: On dry fermented sausages, especially co‐extruded with calcium alginate casings, the formation of white crystals on the surface of the product is a common problem. In this study a hurdle system of combinations of different metal complexing chelators (citric acid and polyphosphate) was investigated. The control and the sample produced with 1.1% citric acid in the alginate gel showed strong white efflorescence formation during the storage (∼60% of the surface was covered), whereas the samples with added 0.3% polyphosphate showed no efflorescence formation. The efflorescence‐causing substances such as lactate, magnesium, and calcium increased significantly in the samples, which showed the strongest white efflorescence formation. In the control, lactate increased by 45.0%, calcium by 23.9%, and magnesium by 150.8%, whereas in the samples without white efflorescence, the magnesium and lactate content increased only slightly, and the calcium content even decreased during the storage of 8 weeks. The best results were observed on the addition of 0.3% polyphosphates and the citric acid surface treatment directly after the co‐extrusion. Moreover, the strong complex formation could be due to the complexation of magnesium and calcium by lactate, whereby they are removed from the diffusion equilibrium leading to an increased diffusion of the efflorescence‐causing substances. Practical Application: White efflorescence formation on dry fermented sausages is a major problem on dry fermented sausages, which causes food waste and financial loss for the producer. This study investigated different combinations of promising methods and it was possible to inhibit the white efflorescence formation during the storage. The methods are easy to implement during the manufacturing of the products and are therefore quite interesting for the industrial applications.